ANALISIS KESALAHAN PENGGUNAAN JOSHI “WA” DAN “GA” PADA MAHASISWA TINGKAT III PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU T.A 2017/2018 - Oktaviani, Putri; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses about the errors of using Wa and Ga particle carried out by third grade student japanese education program FKIP Riau University Academic Year 2017/2018. The purpose of this research was to find out and describe the errors in the use of wa and ga particle on what functions were most often performed by students and how students understood the use of wa and ga particle in Japanese sentences. This research is descriptive qualitative, to obtain data, the instrument used in this research is a written test. The object of this research is third grade student japanese education program FKIP Riau University Academic Year 2017/2018 who have passed the bunpou 4 courses which are 32 students. Based on the results of the test, students made more mistakes in the use of wa particle than ga particle. Student errors in the use of wa particle occur mostly in functions to show a thing that contrasts/contradicts what is said behind it (100%) and functions as a topic marker in negative sentences (90,6%). Student errors in the use of ga particle occur mostly in functions to affirm the subject (90,6%) and function to show the subject of intransitive verbs (84,3%).Key Words: Error analysis, Wa and Ga particle